Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1590/s0102-35862001000600002
|View full text |Cite
|
Sign up to set email alerts
|

Teste da caminhada de seis minutos em pacientes com DPOC durante programa de reabilitação

Abstract: 295Conclusão: Sugere-se utilizar-se metodologia padronizada e adequada para realização do TC6, inclusive quando o objetivo for obter valores de referência. As equações de Enright e Sherril para indivíduos normais parecem tender a valores subestimados, não diferindo estatisticamente dos valores obtidos pré-treinamento nesses pacientes com DPOC. Isso se deve, provavelmente, a diferenças na técnica de encorajamento utilizada pelos autores. Confirma-se o ganho de performance física, após reabilitação, independente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0
10

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 9 publications
(8 reference statements)
3
3
0
10
Order By: Relevance
“…(28) With the inclusion of patients with similar characteristics, another study revealed that the 6MWT should be recommended for COPD patients enrolled in rehabilitation programs. (29) The results obtained in that study did not differ from those reported by Enright & Sherrill. (7,29) …”
Section: Validation In Pediatricssupporting
confidence: 41%
See 1 more Smart Citation
“…(28) With the inclusion of patients with similar characteristics, another study revealed that the 6MWT should be recommended for COPD patients enrolled in rehabilitation programs. (29) The results obtained in that study did not differ from those reported by Enright & Sherrill. (7,29) …”
Section: Validation In Pediatricssupporting
confidence: 41%
“…(29) The results obtained in that study did not differ from those reported by Enright & Sherrill. (7,29) …”
Section: Validation In Pediatricssupporting
confidence: 41%
“…In accordance with previous reports in the literature, (4,13) there was no significant alteration of the obstruction. Therefore, this improvement might be explained by the decrease in pulmonary inflation, although that parameter was not evaluated after the ET program.…”
Section: Introductionsupporting
confidence: 93%
“…It is based on a routine activity, the walk, and easily accepted by the patients (12,13,14). The 6MWT is being an increasingly used form of adjuvant or alternative evaluation of cardiac patients (13).…”
Section: Introductionmentioning
confidence: 99%